2022
DOI: 10.1177/20584601221107345
|View full text |Cite
|
Sign up to set email alerts
|

Observer performance evaluation of the feasibility of a deep learning model to detect cardiomegaly on chest radiographs

Abstract: Background Cardiothoracic ratio (CTR) is the ratio of the diameter of the heart to the diameter of the thorax. An abnormal CTR (>0.55) is often an indicator of an underlying pathological condition. The accurate prediction of an abnormal CTR chest X-rays (CXRs) aids in the early diagnosis of clinical conditions. Purpose We propose a deep learning (DL)-based model for automatic CTR calculation to assist radiologists with rapid diagnosis of cardiomegaly and thus optimise the radiology flow. Material and Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Then, the CTR can be calculated accordingly by traditional methods. Similar methods have been shown to be accurate and effective [ 12 , 13 , 14 , 15 , 16 ] in previous works. However, hemodialysis patients are predisposed to a considerable prevalence of pulmonary complications (e.g., pulmonary edema 8.20–20.50%, pleural effusions 22.95–33.80%) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Then, the CTR can be calculated accordingly by traditional methods. Similar methods have been shown to be accurate and effective [ 12 , 13 , 14 , 15 , 16 ] in previous works. However, hemodialysis patients are predisposed to a considerable prevalence of pulmonary complications (e.g., pulmonary edema 8.20–20.50%, pleural effusions 22.95–33.80%) [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 69%
“…Previous studies have shown that CTRs determined by segmentation-based methods using deep learning can identify cardiomegaly with good accuracy [ 12 , 13 , 14 , 30 ]. The CXRs of the general population were selected for model training, validation, and testing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a different study, the performance of radiologists in detecting cardiomegaly was assessed using the Attention U-Net deep learning architecture, which calculated the cardiothoracic ratio (CTR). The study revealed a moderate level of agreement, with a Kappa value of 0.506 [ 29 ]. Although our work is not directly comparable, the use of agreement statistics allows for comparison with both human readers and AI models.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ajmera et al also deployed U-Net for segmenting areas of lungs and heart [16]. The CTR was calculated using widths of chest and heart.…”
Section: Introductionmentioning
confidence: 99%